Permasalahan Yang Dialami Lansia Dalam Menyesuaikan Diri Terhadap Penguasaan Tugas-Tugas Perkembangannya - Afrizal, Afrizal (Sekolah Tinggi Agama Islam (STAIN) Curup, 2018)
The purpose of this study is to describe and illustrate the problems experienced by the elderly in mastering development tasks. This research is a research field that is qualitative, descriptive. From the results of research can be in the know that, physical strength and health is a major problem that is often faced by the elderly, because the family needs still great while power on the wane so what generated the leter insufficient, retirement is not a lot of problems arise that relate to economic families in meeting the daily needs, the problem of death of spouse is a very heavy problems perceived by the elderly because they often living areas a sense of loneliness and changing roles between them, in forming a relationship with people at not too experienced obstacles, because the elderly usually often follows the recitation or arisan, problems associated with the broader social role is not too experienced a lot of problems, because the elderly are still arriving by the whole community.